2021
DOI: 10.1111/jan.14734
|View full text |Cite
|
Sign up to set email alerts
|

A model of culturally‐informed integrated diabetes education and eye screening in indigenous primary care services and specialist diabetes clinics: Study protocol

Abstract: Aims To improve diabetes management in Indigenous Australians using an integrated nurse‐led model of diabetes education and eye screening in indigenous primary care and specialist diabetes clinics. Design A pre–post study. Methods This study will be implemented in indigenous primary care and specialist diabetes clinics in Victoria, Australia. Participants recruited to the study will be existing adult patient with diagnosed diabetes attending study sites. A nurse‐credentialled diabetes educator and certified re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Certified retinal imagers and diabetes educators whilst part of the iDEES study protocol can be replaced with locally trained retinal imagers and diabetes educators who could be nurses, community health workers, clinicians or allied health professionals. The tasks undertaken by the nurse in the iDEES protocol are shown in Figure S1 and the detailed imaging protocol is described in the iDEES protocol manuscript (Atkinson‐Briggs et al, 2021). This information allows nurses without additional diabetes qualifications and experience to learn from the novel iDEES model of education based on eye‐screening, which is now a service being promoted by the peak body for CDEs, the Australian Diabetes Educators Association (ADEA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certified retinal imagers and diabetes educators whilst part of the iDEES study protocol can be replaced with locally trained retinal imagers and diabetes educators who could be nurses, community health workers, clinicians or allied health professionals. The tasks undertaken by the nurse in the iDEES protocol are shown in Figure S1 and the detailed imaging protocol is described in the iDEES protocol manuscript (Atkinson‐Briggs et al, 2021). This information allows nurses without additional diabetes qualifications and experience to learn from the novel iDEES model of education based on eye‐screening, which is now a service being promoted by the peak body for CDEs, the Australian Diabetes Educators Association (ADEA).…”
Section: Discussionmentioning
confidence: 99%
“…Data collection and management are detailed in the published protocol paper (Atkinson‐Briggs et al, 2021. Briefly, the nurse PI obtained demographic and selected clinical data, including the date of the last eye examination if recorded, and presenting visual acuity was assessed.…”
Section: The Studymentioning
confidence: 99%
“…This reveals the urgent need for educational activities that instruct patients on basic eye care knowledge, such as health lectures and health education at health care institutions of all levels (e.g., through media and posters). In addition, previous studies have found that comprehensive education models combining diabetes education and ophthalmic screening can promote timelier DR screening, referral, and treatment of vision-threatening retinopathy (Atkinson-Briggs et al, 2021). Another reason for patients' lack of knowledge may be that DR can develop silently.…”
Section: Discussionmentioning
confidence: 99%
“…(6) A pre-post study was conducted in Australia, to see improvements in diabetes management using Nurse led model of diabetes education and supported that there model will improve adherence to the best practices and recommendations regarding health promotion, risk factor modifications and self-management of diabetes. (7) Results of a meta-analysis published in 2022 observed a positive impact on HBa1c , cardiac markers and risk factors modifications, when diabetes specialists were integrated in a working plan with primary health care professionals. (8) Another study in Philippines (2022), addressed the issue as Diabetes ecosystem and concluded that efforts can evolve a diabetes ecosystem, which involves awareness compaigns , screening activities, early and accurate diagnosis and affordable treatment plans.…”
Section: Introductionmentioning
confidence: 99%